Cartoon folder cover - front page (in French) - Novossiolova, Tatyana; Dando, Malcolm; Shang, Lijun; Zanders, Jean Pascal (2021)
This is the French version of the front cover for a series of cartoons about the development and promotion of biological and chemical security education in the Higher Education sector.